Process analysis for structural optimisation of thermoplastic composite component using the building block approach. (1st October 2017) - Jayasree, N. Amirth; Airale, A.G.; Ferraris, A.; Messana, A.; Sisca, L.; Carello, M.
Abstract: The paper aim is to establish and optimise the prediction model of a thermoplastic fibre reinforced component designed and manufactured through an integrated injection moulding process (Hybrid Moulding). This is done by the Finite Element Analysis (FEA) and then the process simulations, considering the composite material as an elastic anisotropic woven fabric to study the deformations undergone during the manufacturing process. The proposed methodology for creating the predictive model is fairly accurate, and it is a novel method which can be easily integrated and adapted into a components initial design phase. This optimisation technique can replace the expensive and traditional trial and error procedures during the design and prototyping phase, and it significantly decreases the time to build the final component. The final scope of the research is to simplify the product development phase of general lightweight automotive thermoplastic components by creating an innovative methodology for predictive modelling.